Statistical Methods for the Investigation of Solvolysis Mechanisms Illustrated by the Chlorides of the Carbomethoxy Protecting Groups NVOC and FMOC - Malcolm J. D’Souza; Jasbir K. Deol; Maryeah T. Pavey; Dennis N. Kevill (Journal of Analytical Methods in Chemistry)
The solvolysis of 4,5-dimethoxy-2-nitrobenzyl chloroformate (NVOC-Cl, 1) is followed at 25.0°C in twenty hydroxylic solvents. A comparison with previously published rates for benzyl chloroformate and p-nitrobenzyl chloroformate indicates that the inductive effect of the nitro and the two methoxy groups strongly influences the rate of reaction. For 1, the specific rates of solvolysis are correlated using an extended Grunwald-Winstein (G-W) treatment. A direct comparison with the data for phenyl chloroformate (PhOCOCl) in identical solvents strongly suggests that the addition step within an addition-elimination mechanism is rate-determining for both substrates. A reevaluation of the kinetic data for 9-fluorenylmethyl chloroformate (FMOC-Cl, 2) involves a correlation of log⁡k/ko2 versus log⁡(k/ko)PhOCOCl. In this plot, deviations were observed in solvents rich in a hydrogen-bonding fluoroalcohol component. Omitting the aqueous fluoroalcohol rate measurements for 2 in an analysis using the extended G-W equation suggested the occurrence of dual pathways differing in the dependences upon the ionizing power and nucleophilicity of the solvent. In addition, the fluorenyl ring is rotated out of the plane containing the ether oxygen and, as a result, PhOCOCl is found to solvolyze 20 times faster than 2 in ethanol and methanol.